Developing a context-relevant psychosocial stimulation intervention to promote cognitive development of children with severe acute malnutrition in Mwanza, Tanzania. - Cecilie L Jensen; Erica Sanga; Heather Kitt; George PrayGod; Happiness Kunzi; Theresia Setebe; Suzanne Filteau; Jayne Webster; Melissa Gladstone; Mette F Olsen (PLoS ONE, 2024)
More than 250 million children will not meet their developmental potential due to poverty and malnutrition. Psychosocial stimulation has shown promising effects for improving development in children exposed to severe acute malnutrition (SAM) but programs are rarely implemented. In this study, we used qualitative methods to inform the development of a psychosocial stimulation programme to be integrated with SAM treatment in Mwanza, Tanzania. We conducted in-depth interviews with seven caregivers of children recently treated for SAM and nine professionals in early child development. We used thematic content analysis and group feedback sessions and organised our results within the Nurturing Care Framework. Common barriers to stimulate child development included financial and food insecurity, competing time demands, low awareness about importance of responsive caregiving and stimulating environment, poor father involvement, and gender inequality. Caregivers and professionals suggested that community-based support after SAM treatment and counselling on psychosocial stimulation would be helpful, e.g., how to create homemade toys and stimulate through involvement in everyday chores. Based on the findings of this study we developed a context-relevant psychosocial stimulation programme. Some issues identified were structural highlighting the need for programmes to be linked with broader supportive initiatives.